Optimalisasi Kinerja Keuangan Usaha Kuliner Melalui Implementasi QRIS - Evi Dewi Kusumawati; Dewi Kartikasari (Politeknik Ganesha Medan, 2025)
This study investigates how the implementation of Quick Response Code Indonesian Standard (QRIS) impacts the financial performance of micro, small, and medium enterprises (MSMEs) in the Surakarta culinary industry, considering data quality and financial management effectiveness as moderating variables. In the culinary industry, QRIS has become popular because it facilitates digital transactions. The purpose of this study is to determine whether the implementation of QRIS can help improve the financial performance of culinary businesses by considering the increasing use of QRIS in Indonesia, to investigates the functions of data quality and financial management effectiveness as factors that can influence how QRIS implementation impacts financial performance. This study involved a population of 200 culinary MSMEs in Surakarta, of which 100 respondents were selected as respondents through a simple random sampling method. This research applies a quantitative approach. The analysis was conducted with moderation regression using SPSS. The results show that the implementation of QRIS significantly improves the financial performance of MSMEs, especially in terms of increasing operating productivity and revenue. Data quality shows that inaccurate or difficult-to-access data can hinder performance. Conversely, good results from financial management have a positive impact, showing how important it is to have good financial management capabilities. Financial performance is strengthened by the relationship between QRIS implementation and financial management effectiveness, as is the relationship between data quality and financial management effectiveness. This study found that the financial performance of culinary MSMEs can be improved by implementing QRIS along with high-quality data and effective financial management.